The effects of intermittent theta burst stimulation of the unilateral cerebellar hemisphere on swallowing-related brain regions in healthy subjects - Wang, Bingyan; Sun, Hui; Pan, Xiaona; Ma, Wenshuai; Dong, Linghui; Wang, Qiang; Meng, Pingping (Frontiers in Human Neuroscience, 2023)
Objective: We aimed to investigate the effects and mechanisms of swallowing-related brain regions using resting-state functional magnetic resonance imaging (rs-fMRI) in healthy subjects who underwent intermittent theta burst stimulation (iTBS) on dominant or non-dominant cerebellar hemispheres. Method: Thirty-nine healthy subjects were randomized into three groups that completed different iTBS protocols(dominant cerebellum group, non-dominant cerebellum group and control group). Before iTBS, the resting motor threshold (rMT) was measured by single-pulse transcranial magnetic stimulation (sTMS) on the cerebellar representation of the suprahyoid muscles, and the dominant cerebellar hemisphere for swallowing was determined. Forty-eight hours after elution, iTBS protocols were completed: in the dominant cerebellum group, iTBS was administered to the dominant cerebellar hemisphere, and the non-dominant cerebellar hemisphere was given sham stimulation; in the non-dominant cerebellum group, iTBS was administered to the non-dominant cerebellar hemisphere, and sham stimulation was delivered to the dominant cerebellar hemisphere; in the control group, sham stimulation was applied to the cerebellum bilaterally. Rs-fMRI was performed before and after iTBS stimulation to observe changes in the amplitude of low-frequency fluctuation (ALFF) in the whole brain. Results: Compared with baseline, the dominant cerebellum group showed increased ALFF in the ipsilateral cerebellum, and decreased ALFF in the ipsilateral middle temporal gyrus and contralateral precuneus after iTBS; the iTBS of the non-dominant cerebellum group induced increased ALFF in the ipsilateral superior frontal gyrus, the calcarine fissure and the surrounding cortex, and the contralateral inferior parietal lobule; and in the control group, there was no significant difference in ALFF. Exploring the effects induced by iTBS among groups, the dominant cerebellum group showed increased ALFF in the ipsilateral superior temporal gyrus compared with the non-dominant cerebellum group. Conclusion: Intermittent theta burst stimulation of the domnant cerebellar hemisphere for swallowing excited the ipsilateral cerebellum, and stimulation of the non-dominant cerebellar hemisphere increased the spontaneous neural activity of multiple cerebrocortical areas related to swallowing. In conclusion, regardless of which side of the cerebellum is stimulated, iTBS can facilitate part of the brain neural network related to swallowing. Our findings provide supporting evidence that cerebellar iTBS can be used as a treatment method for poststroke dysphagia.